Analysis of erythrocyte membrane proteins in patients with hereditary spherocytosis and other types of haemolytic anaemia. Issue 9 (21st October 2018) - Shibuya, Atsushi; Kawashima, Hiroaki; Tanaka, Masato
ABSTRACT: Objectives: In order to investigate the pathophysiology of erythrocyte membrane proteins, 10 patients (6 pre- and 4 post-splenectomy) with hereditary spherocytosis (HS) and other patients with haemolytic anaemia were examined. Methods: The membrane proteins were analysed by biochemical and mass spectrometry. Results: Reductions in the extracellular membrane of band 3 protein by eosin-5'-maleimide (EMA) binding test were greater in patients with pre-splenectomy HS than in patients with post-splenectomy HS, other types of haemolytic anaemia, and controls. Compared to patients with haemolytic anaemia and healthy controls, the band 3 protein of patients with HS pre- or post-splenectomy was more easily decomposed with N-glycosidase F and by mass spectrometry interactions with degraded low-molecular-weight spectrin and ankyrin. The resulting fragments were observed more frequently in pre-splenectomy than post-splenectomy HS. Haemoglobin-derived peptides were present in patients with haemoglobinopathy (Hb Evans, Hb Sabine) but not in those with haemolytic anaemia and healthy controls. Conclusion: Haemolysis in patients with HS occurred because the fragile proteins in erythrocytes (band 3, spectrin, and ankyrin) collapsed due to compression during blood circulation in the spleen. Further, haemolysis in patients with haemoglobinopathy occurred owing to membrane damage due to combined spectrin, band 3 with denatured haemoglobin in the vessel during blood circulation.